2021
DOI: 10.3390/cancers13133122
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Replication-Dependent Histone Signifies a Subset of Dedifferentiated Liposarcoma with Increased Aggressiveness

Abstract: Liposarcoma (LPS) is an adult soft tissue malignancy that arises from fat tissue, where well-differentiated (WD) and dedifferentiated (DD) forms are the most common. DDLPS represents the progression of WDLPS into a more aggressive high-grade and metastatic form. Although a few DNA copy-number amplifications are known to be specifically found in WD- or DDLPS, systematic genetic differences that signify subtype determination between WDLPS and DDLPS remain unclear. Here, we profiled the genome and transcriptome o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…FL-AR activity is further substantiated by the current study where depletion of the FL-AR elevates expression of multiple histone transcripts. The consequences of an abrupt elevation of multiple histones are not well studied, but in yeast abnormal histone accumulation interferes with chromosome segregation and promotes whole genome duplication 39 , while overexpression of replication-dependent histone genes confers malignancy to dedifferentiated liposarcoma 40 . Restraining FL-AR in the BlCa context may have similar consequences, but this needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…FL-AR activity is further substantiated by the current study where depletion of the FL-AR elevates expression of multiple histone transcripts. The consequences of an abrupt elevation of multiple histones are not well studied, but in yeast abnormal histone accumulation interferes with chromosome segregation and promotes whole genome duplication 39 , while overexpression of replication-dependent histone genes confers malignancy to dedifferentiated liposarcoma 40 . Restraining FL-AR in the BlCa context may have similar consequences, but this needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…In glioma, a HMGA2/GCN5 protein complex promoted histone acetylation in nucleosomes at AT-rich DNA sites, to cause gene activation of matrix metalloproteinase 2 (MMP2), a mediator of invasiveness in glioma, and conferring a poor prognosis [ 80 ]. Overexpression of HMGA2 coincided with elevated levels of H2A, H2B, H3, and H4 core histones in a subpopulation of dedifferentiated liposarcoma, again conferring a poor prognosis [ 81 ]. An even more intricate HMGA2-histone relationship is suggested by recent evidence that demonstrates the requirement for HMGA2 to induce DNA nicks to facilitate the incorporation of phosphorylated H2A.XS139 isoform (γ-H2AX) into nucleosomes to earmark DNA sites for repair-mediated DNA demethylation and transcription activation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using this model, the researchers effectively demonstrated that by inducing the expression of Yamanaka factors (OSK), they could successfully reprogram the epigenetic profile to resemble a more youthful state, thereby restoring the normal histone expression [30]. Together, these studies showed that certain regulatory factors play a central role in the expression of histone genes, and tweaking the expression of these master regulators could attenuate or accentuate the histone levels [60,[198][199][200][201].…”
Section: Histone Complementation In Cells Experiencing Histone Lossmentioning
confidence: 99%